Model Pengelolaan Aset Wakaf Berbasis Profesionalisme Nadzir di Kecamatan Mamajang Kota Makassar - Nurul Rahmania; Wardatul Jannah; A. Syatir Sofyan (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2020)
This study seeks to provide an overview of an effective strategy for waqf asset management through a model recommendation in Mamajang District, Makasar City. The low quality of human resources, in this case is nadzir in managing waqf assets, causes waqf to be unproductive in Indonesia. Therefore, the purpose of this study is to provide an overview to the parties concerned, in this case waqf, regarding the unproductive nature of waqf in Indonesia so far so that it can be taken into consideration for the increase of waqf in the future. This type of research is descriptive qualitative. The results obtained are Nazhir in the district. Mamajang does not carry out its duties according to the existing law. The donation process carried out in the district. Mamajang is only intended for the construction of religious facilities and there are still waqf lands that have not been certified due to problems with Nazhir in managing land certificates that do not exist.